Pengaruh Free Cash Flow, Company Growth, Collateralizable Asset dan Institusional Ownership terhadap Kebijakan Dividen - Marsela, Vinka; Azzahra, Khoirunnisa (JURNAL AKUNTANSI BARELANG, 2024)
This research aims to provide emprical evidence that there is an influence of the of free cash flow, company growth, collateralizable assets, and institusional ownership on divedend policy in properties and real estate sector companies listed on the IDX (Indonesia Stock Exchange) for the 2018 -2022 period. The number of research samples is 7 sector companies properties and real estate determined based on the purposive sampling method. The method used is multiple linear regression, descriptive statistical test, panel data regression model analysis, fiexed effect model selection test, classical assumption test, multiple linear test and hypothesis test with the help of e-views version 12 statistical data processing. The results of this research show that free cash flow, company growth, collateralizable assets and institusional ownership simultaneously have a significant effect on dividen policy and the t test states thas free cash flow has a significant effect on dividen policy. The variables company growth, collateralizable assets, and institusional ownership have no effect significant to dividen policy.